SLAVIC ELEMENTS IN THE NAMES OF CONTEMPORARY INHABITANTS OF VIĻĀNI (EASTERN LATVIA) - Rembiszewska, Dorota Krystyna; Sikora, Kazimierz (Via Latgalica, 2017)
The article depicts some distinctive features present in the anthroponymic system of the inhabitants of Viļāni, a town in eastern Latvia known for the former Slavic (Polish, Russian, Belarusian) settlements. Personal names are evidence of coexistence of several nations and of the overlapping of various cultural and linguistic influences in the area of Latgale. 500 surnames, excerpted from a list of 1100, demonstrate their Slavic origin. The article discusses assimilation processes, including graphic changes that result from the process of adaptation of Slavic names to Latvian, and analyses typical Slavic suffixes used to derive personal names (-wski, -ko, -owicz). This research deals with the difficulty of unequivocal attribution of some surnames to a specific Slavic language. One of the sources of this research is 19th-century records with the names of the inhabitants of Viļāni drawn up by Stefania Ulanowska, author of “Łotysze Inflant Polskich” (1891–1895).